Pengaruh Penggunaan Buku Paket Terhadap Hasil Belajar Siswa SD - Abay Rostika (Universitas Mathla'ul Anwar Banten, 2016)
This study aims to determine the effect of handbook towards students’ result. A method of data collection is done through pre-test and post-test using a quantitative approach. This study used an experimental design. The data analysis technique used is quantitative descriptive. Results of the data analysis showed that the price of the tcount of 2,826 and 2,000 ttable with significance α=0.05 and df 58. Then to test the hypothesis, H0 refused and H1 accepted. This shows that the use of hand book has an enormous influence on students’ result.